Just Harriet - Arnold, Elana K.; Ho, Dung (New York, NY Walden Pond Press, 2022)
"There are a few things you should know about Harriet Wermer: She just finished third grade. She has a perfect cat named Matzo Ball. She doesn't always tell the truth. She is very happy to be spending summer vacation away from home and her mom and dad and all the wonderful things she had been planning all year. Okay, maybe that last one isn't entirely the truth. Of course, there's nothing Harriet doesn't like about Marble Island, the small island off the coast of California where her nanu runs a cozy little bed and breakfast. And nobody doesn't love Moneypenny, Nanu's old basset hound. But Harriet doesn't like the fact that Dad made this decision without even asking her. When Harriet arrives on Marble Island, however, she discovers that it's full of surprises, and even a mystery. One that seems to involve her Dad, back when he was a young boy living on Marble Island. One that Harriet is absolutely going to solve. And that's the truth."--
Ages 6-10.
Grades 2-3.
113584
Keywords: Girls; Summer; Grandmothers; Families; Family secrets; Bed and breakfast accommodations; Vacations; Mystery and detective stories; Family life; Fictional Work; Domestic fiction